REDESIGN OF THE APPOINTMENT OF ACTING OFFICERS IN FILLING THE VACANCY OF THE DEMOCRATIC REGIONAL HEAD POSITION - Barok Pratama, Agung; Imaduddin, Aufi; Asyria Yamin, Tsinta; Yusron Rofi'i, Hilmi; Leo Saputra, Aldila; Pratama, Agung Barok; Putri, Sofi Ekiana (JURNAL TAPIS, 2025)
This study aims to describe the (existing) appointment of acting regional heads to fill vacant permanent regional head positions and to propose the ideal appointment of acting regional heads based on democratic principles as stipulated in Law No. 10/2016 on Regional Elections. This study is a normative legal study using a legal and conceptual approach. The data obtained are analyzed and interpreted using relevant legal interpretation methods, and deductive conclusions are drawn. The results of this study indicate that the acting governor who will fill the vacant position will be directly appointed by the President based on the submission of names from the Ministry of Home Affairs (Kemendagri). As for Acting Regents and Mayors, they are directly selected by the Ministry of Home Affairs. A more democratic appointment design is proposed by implementing a merit-based system in recruitment and broader participation from various political parties, including the Regional People's Representative Council (DPRD). This more democratic design aims to ensure the appointment process is more transparent, accountable, and aligned with democratic principles and regional aspirations.